Detection and analysis of vegetation cover changes in the city of M'Sila, Algeria, between the years 1990-2023 using the NDVI (Normalized Difference Vegetation Index) - Dogha, Mohamed Soufiane; Faid, Bachir (Brawijaya University, 2025)
This study aimed to monitor and evaluate the change in the vegetation cover of the city of M'Sila based on calculating the Normalized Difference Vegetation Index (NDVI) linked to Landsat satellite image data for the years 1990-2023 and measuring the change for approximately every 10 years. The region was classified based on the index values ??into two categories: an area free of vegetation cover and an area containing vegetation cover. The results showed a difference in the area and density of vegetation cover by increasing the area of ??vegetation cover at different rates of change according to the three periods, respectively 45.98%, 6.66%, and 6.87%, which led to an increase in the area classified as vegetation cover according to the three periods 1.89 km2, 0.4 km2, 0.44 km2, with an average annual change estimated at 0.19 km2/year, 0.04 km2/year, 0.03 km2/year, where the percentage of vegetation cover in 1990 was about 8.70% of the total area of ??the city, while in 2023 it increased to record a percentage of 14.48%. This study showed the possibility of using remote sensing techniques and geographic information systems to provide valuable basic spatial information to support monitoring of vegetation cover, identifying areas exposed to environmental risks and threats, and thus developing strategies for adaptation and conservation of the ecosystems and natural resources of the study area.